Tagging of genomic STAT3 and STAT1 with fluorescent proteins and insertion of a luciferase reporter in the cyclin D1 gene provides a modified A549 cell line to screen for selective STAT3 inhibitors. - Andrey Samsonov (Public Library of Science (PLoS), 2013)
Signal transducer and activator of transcription 3 (STAT3) is an oncogenic protein that is constitutively activated in numerous cancer cell lines and human cancers. Another STAT family member, STAT1, possesses cancer-inhibitory properties and can promote apoptosis in tumor cells upon activation. To better characterize these important cancer related genes, we tagged STAT3 and STAT1 loci with fluorescent protein (FP) sequences (RFP and GFP respectively) by targeted integration via zinc finger nuclease (ZFN)--mediated homologous recombination in A549 cells that express aberrantly activated STAT3. We inserted the FP transgenes at the N-terminus of the STAT3 locus and at the C-terminus of the STAT1 locus. The integration resulted in endogenous expression of fluorescent STAT3 and STAT1 chimeric fusion proteins. When stimulated with IL-6 or IFN-γ, the cells showed robust nuclear translocation of RFP-STAT3 or STAT1-GFP, respectively. Pre-incubation of cells with a known specific STAT3 inhibitor showed that IFN-γ-induced translocation of STAT1-GFP was not impaired. STAT3 activates multiple downstream targets such as genes involved in cell cycle progression - e.g. cyclin D1. To detect changes in expression of endogenous cyclin D1, we used ZFN technology to insert a secreted luciferase reporter behind the cyclin D1 promoter and separated the luciferase and cyclin D1 coding regions by a 2A sequence to induce a translational skip. The luciferase insertion was made in the RFP-STAT3/STAT1-GFP cell line to have all three reporters in a single cell line. Addition of a STAT3 inhibitor led to suppression of cyclin D1 promoter activity and cell growth arrest. The triple-modified cell line provides a simple and convenient method for high-content screening and pre-clinical testing of potential STAT3 inhibitors in live cells while ensuring that the STAT1 pathway is not affected. This approach of reporting endogenous gene activities using ZFN technology could be applied to other cancer targets.